QOLP-10. PATIENT-REPORTED OUTCOMES DURING TREATMENT FOR GLIOBLASTOMA: SYMPTOM BURDEN AND ASSOCIATED IMPACT ON DAILY LIFE. (11th November 2019) - Hultman, Meghan; Tipps, Megan; Liu, Minda; Banerji, Nilanjana; Bruns, Patricia; Trusheim, John
Abstract: INTRODUCTION: Glioblastoma is the most common primary malignant brain tumor, with an annual incidence of 3–4 new cases per 100, 000 people. Despite advances in chemotherapy, radiotherapy, and surgical interventions, prognosis remains poor. Aims of treatment for life-limiting diagnoses should extend beyond increasing survival time to include palliation of symptoms and promotion of quality of life. Here we describe patient-reported symptoms both early and late in the glioblastoma treatment trajectory, as well as their associated interference with daily life. METHODS: Fifty patients with newly diagnosed glioblastoma were recruited between September 2015-March 2018. Demographic and clinical information was collected from medical records. Patients also completed the brain tumor-specific MD Anderson Symptom Inventory (MDASI-BT) approximately every 8 weeks from completion of chemoradiation through cessation of active disease treatment. Both individual and categories of related symptoms reported in the initial two (early treatment) and final two (late treatment) MDASI-BT assessments were examined for symptom frequency, severity, and relationships between symptom severity and interference with daily life. Patients still receiving treatment or who completed < 4 total MDASI-BT assessments were excluded from the analysis. RESULTS: The most commonly reported symptoms were often, but not always, consistent with the symptoms rated as most severe. This was true for individual symptoms as well as categories of symptoms. The most common/severe symptoms also changed from early to late treatment. Overall symptom burden was positively correlated with symptom interference in daily life (r=0.67, p< 0.0001). Regression analysis identified different symptoms as predictors of interference in early as opposed to late treatment, and these predictors did not necessarily align with the most common/severe symptoms. CONCLUSION: Symptom experience for patients with glioblastoma is complex and dynamic. Attention to symptom trajectories for patients with glioblastoma may direct approaches to assessment, early identification, and symptom management, thus promoting better quality of life.